2007
DOI: 10.1016/j.aquaculture.2007.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids vs. neutral lipids: Effects on digestive enzymes in Atlantic cod (Gadus morhua) larvae

Abstract: The aim of this study was to evaluate the effect of dietary lipid classes (phospholipid vs. neutral lipid) and level of n-3 highly unsaturated fatty acids (HUFAs) on growth, survival and digestive enzymatic activity in Atlantic cod (Gadus morhua) larvae. Larvae were fed enriched rotifers from mouth opening and were weaned to formulated diets during a co-feeding period lasting from 17 days post hatch (dph) to 24 dph. Larvae were fed exclusively compound diets from 24 dph until the end of the experiment. Three i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 49 publications
5
37
1
1
Order By: Relevance
“…The total length/weight increased progressively since birth until the third stage (18 days), when seahorses needed to use energy also to develop physiological systems. Unlike happen in pelagic fish (Santamaría et al 2004;Wold et al 2007), higher rates of growth were (Cañavate et al 2006), with values that decreasing after the metamorphosis. This fact occurs also in H. reidi during the 4th stage, mainly characterized by the growth of the pre-existing structures.…”
Section: Discussioncontrasting
confidence: 48%
“…The total length/weight increased progressively since birth until the third stage (18 days), when seahorses needed to use energy also to develop physiological systems. Unlike happen in pelagic fish (Santamaría et al 2004;Wold et al 2007), higher rates of growth were (Cañavate et al 2006), with values that decreasing after the metamorphosis. This fact occurs also in H. reidi during the 4th stage, mainly characterized by the growth of the pre-existing structures.…”
Section: Discussioncontrasting
confidence: 48%
“…In the earlier case, CCK levels between 0.5 -1.0 fmol larva -1 found for larval cod of comparable age (to 17 dph in Kortner et al, 2011b) in the present study might be the threshold for the regulatory role of CCK in larval cod. In general, the developmental pattern of different digestive enzymes has been described in several species, including California halibut (Paralichthys californicus) (AlvarezGonzález et al, 2005), sea bass (Cahu and Zambonino Infante, 1994), cobia (Rachycentron canadum) (Faulk et al, 2007), red drum (Sciaenops ocellatus) (Lazo et al, 2000a) and Atlantic cod (Wold et al, 2007) and has been found to be speciesspecific. It has been proposed, that digestive enzyme activities in early stages of marine fish larvae are under transcriptional control, but can be triggered by the nutritional composition of the diet (Zambonino Infante and Cahu, 2001).…”
Section: Ontogenymentioning
confidence: 99%
“…The gut maturation index, based on the relation between individual activity of bbm enzymes and a cytosolic enzyme leu-ala, has been used for evaluation of intestinal maturation in fish larvae, as higher ratios denote the more advanced enterocyte development (Cahu and Zambonino Infante 1995;Cahu et al 1999;Ribeiro et al 2002;Ma et al 2005;Wold et al 2007;Zouiten et al 2008). The significantly lower ratio of bbm LAP/leu-ala in treatments NRD-8 and NRD-13 on 28 dph showed that enterocytes of the larvae in these treatments were less matured than in the LF treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Also, Lazo et al (2000b) were able to obtain good growth and survival in red drum Sciaenops ocellatus larvae fed a compound diet from first feeding with addition of micro algae in the rearing tank. Complete elimination of Artemia by weaning of fish larvae onto microdiets directly from rotifers with acceptable survival and/or growth rate has been reported for red drum Sciaenops ocellatus (Holt 1993), cod Gadus morhua (Baskerville-Bridges and Kling 2000; Rosenlund and Halldorsson 2007;Wold et al 2007) and Asia sea bass Lates calcarifer (Curnow et al 2006a, b).…”
Section: Introductionmentioning
confidence: 95%